(3OjhGf GHf MLQ GdYSbdGfj (B((3efXhe GdOQQ(B)s - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s ((3eMeO GdNaGLj GdNQRLj s)
(3ChdgG (B:s
(3CeG HYO(B: (3MeOkG ddg Ydi EMSGfg abO SFdJ ZjQ eQI Cf CLQO ef efXhej efJNHkG, hCf CaQO ef ebGWjYj eG cGf efgG eQbUkG heWQHG s
(3BNQgG (B:s
(3ef GdebGWY, hbGd(B: (3GdCQV OGQj EPG eG QCjJ QRbkG gfjG Ef WGH YjTj HCQV CbeJ ajgG edjG s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B80 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B765s
Keywords: (3GdCOHs